2021
DOI: 10.3390/ijms22073493
|View full text |Cite
|
Sign up to set email alerts
|

Challenging Hurdles of Current Targeting in Glioblastoma: A Focus on Immunotherapeutic Strategies

Abstract: Glioblastoma is the most frequent primary neoplasm of the central nervous system and still suffers from very poor therapeutic impact. No clear improvements over current standard of care have been made in the last decade. For other cancers, but also for brain metastasis, which harbors a very distinct biology from glioblastoma, immunotherapy has already proven its efficacy. Efforts have been pursued to allow glioblastoma patients to benefit from these new approaches, but the road is still long for broad applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 129 publications
0
8
0
Order By: Relevance
“…At present, the standard of care (SOC) management of GBM is based on the maximum safe surgical removal, radiotherapy, and chemotherapy with temozolomide. However, patients with GBM still have a poor prognosis, and SOC will lead to irreversible toxicity, such as neurological deficits due to surgery, neurocognitive impairments with radiotherapy, and systemic toxicity ( 80 , 81 ). It has been confirmed that immunotherapy is highly effective in inhibiting cancer regression and improving patient quality of life ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…At present, the standard of care (SOC) management of GBM is based on the maximum safe surgical removal, radiotherapy, and chemotherapy with temozolomide. However, patients with GBM still have a poor prognosis, and SOC will lead to irreversible toxicity, such as neurological deficits due to surgery, neurocognitive impairments with radiotherapy, and systemic toxicity ( 80 , 81 ). It has been confirmed that immunotherapy is highly effective in inhibiting cancer regression and improving patient quality of life ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, formulating a standardized DC preparation process will be conducive to produce a better treatment effect. 103 T A B L E 1 Clinical trials of glioma DC vaccines from the perspective of cultured mature DC DTH: Delayed type hypersensitivity; GAA: Glioma associate antigen; GM-CSF: Granulocyte-macrophage colony-stimulating factor; IFN-α: Interferon-α; IFN-γ: Interferon-γ; IL-4: Interleukin-4; IL-6: Interleukin-6; IL-1β: Interleukin-1β; OS: Overall Survival; PFS: Progression-free survival; PGE-2:Prostaglandin E2; poly-IC: Polyinosinic-Polycytidylic acid; TNF-α: Tumor necrosis factor-α; TTP: Time to progression. ICT-107 ↑ : DC pulsed with MAGE-1, HER-2, AIM-2, TRP-2, gp100, and IL-13Rα2…”
Section: Challenge and Methods 1: Standardizing DC Maturation Methodsmentioning
confidence: 99%
“…Therefore, formulating a standardized DC preparation process will be conducive to produce a better treatment effect. 103 …”
Section: Existing Challenges and Future Approaches To DC Immunotherapymentioning
confidence: 99%
“…Two reviews in the Special Issue are addressed to the analysis of current molecular targeting strategies in gliomas. In detail, Genoud and Migliorini focused their attention on immunotherapeutic approaches in glioblastoma [ 6 ]. Glioblastomas, the high-grade gliomas, are the most frequent and aggressive primary tumors of the central nervous system in adults, and no clear improvements over current the standard of care have been made in the last decade.…”
mentioning
confidence: 99%
“…Differently from other neoplasms and brain metastasis, immunotherapy has still not proven its efficacy in gliomas. Genaud and Migliorini reviewed the key glioblastoma immune-related features and the current immunotherapeutic strategies explored with their caveats [ 6 ]. Typical hallmarks of gliomas are molecular alterations of the RTK/PI3K/mTOR axis, and its targeting still represents a strong rationale for developing therapeutic strategies against gliomas.…”
mentioning
confidence: 99%